An Epidemiological Study of Acute Head Injury and It’s Evaluation by CT scan - Ahmad, Md Ziya; Karmakar , R N (Journal of Indian Academy of Forensic Medicine, 2014)
Head injury is a morbid state resulting from gross subtle structural changes in the scalp. Skull  and/or the contents of the skull produce by mechanical forces. The application of blunt force to the head  may result injury to the contents of the skull either alone or with a fracture skull. In six month study period  total 64 cases of head Injuries were admitted in B.C. Roy Hospital. Total number of Male patients  admitted in Hospital due to head Injuries were 46(71.87 %) and female were (28.12%). 32.81% the  victims aged between 21 to 30 years. In present series of study R.T.A. was most common cause of Head  Injury 85.95%. Most common CT finding was Skull fracture 34.37% followed by cerebral contusion  32.81%, extradural hematoma 25% and 21.87 % subarachnoid hemorrhage. CT scan was the main tool  for the imaging the Skull and its contents.
Keywords: CT scan; Head Injury; Extradural Hematoma; Fracture skull